Positive aspects in Cognitive-Behavioral Group Therapy for elderly: a systematic review of the literature (Brazilian Journal of Behavioral and Cognitive Therapy, 2016)
The development of positive aspects of life can contribute to positive aging. To characterize the main objectives of the interventions in Cognitive-Behavioral Group Therapy (CBGT) for elderly and to examine whether positive aspects constitute a focus of them, a systematic review of the literature was conducted. Empirical articles, published between 1998 and 2012, indexed with terms that refer to the practice of CBGT in PsycINFO and PsycARTICLES databases and that included people over 64 years in their samples were selected. 83 researches were recovered. Positive aspects are present in 48.2% of the articles, being Quality/Satisfaction with Life and Coping the most frequent ones. Most of them, however, do not constitute the principal focus of the articles. The scientific production on CBGT for elderly keeps centered in the treatment of psychiatric disorders that is certainly essential, but not sufficient. It is necessary, as proposed by Positive Psychology, that positive aspects also be targets of psychotherapy, thus contributing to positive aging.
Keywords: Positive Aging; Older Adults; Positive Psychology; Cognitive-Behavioral Group Therapy